Production and Economics Evaluation of Pilot Scale Essential Oil Extract from Eucalyptus Citriodora Leaves - Mu’azu, K.; Abubakar, G.; Akuso, A. S.; Mahmood, A.; Sadiq, I. G.; Inuwa, B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
In this study, essential oil was extracted from eucalyptus citriodora leaves plant species (lemon-scented gum) in a pilot plant using steam distillation technology. The extraction pattern of the oil was monitored over time and economic analysis of the production was carried out. Five batches were carried out in a day and the results revealed that the daily production of the oil was 0.579 liters in a loading capacity of 100kg of leaves. It was also observed that the total production cycle per batch was 1.96 hours out of which 80 minutes were the actual extraction time with lag period of 37 minutes. The results further revealed that 66.7% of the oil was extracted in 40 minutes while 95.6% in 80 minutes. Liquefied petroleum gas (LPG) was used as source of energy with daily consumption of 7.5 kg at a cost of N2,400.00K. The economic analysis on annual basis revealed that the operating cost was N1,742,400.00K. The production output of the oil was estimated at 138.96 litres with expected selling price of N4,863,600.00K at the rate of N35,000.00K per litre and expected profit after tax of N2,115,871.00K. From this economic analysis carried out based on the practical data generated in the pilot plant, this project is highly profitable and is strongly recommended to potential investors and entrepreneurs. This will help in providing jobs for our teaming unemployed youths mostly in rural areas where these raw materials are in abundant thereby increasing nation’s foreign earning due to its export potential.